Peran Guru Dalam Mengembangkan Kreativitas Siswa Melalui Pembelajaran Menulis Di Sekolah Dasar - Made Fitriyanti (Jurnal Sultra Elementary School, 2025)
This study aims to describe the teacher’s role in developing students’ creativity through writing instruction in elementary schools. Creativity plays a crucial role in Indonesian language learning as it enables students to express ideas and thoughts in an original, reflective, and meaningful way. This research employs a library research method by reviewing various books, journals, and scientific articles relevant to the topic. The results show that teachers have five main roles in fostering students’ writing creativity: as facilitators, motivators, inspirators, guides, and evaluators. As facilitators, teachers create a conducive learning environment that stimulates creative thinking. As motivators, they build students’ enthusiasm and confidence in writing. As inspirators, teachers provide inspiring examples and writing experiences, while as guides, they assist students in understanding the writing process systematically. Finally, as evaluators, teachers give constructive feedback to improve and appreciate students’ work. These five roles are interrelated and contribute to creating active, reflective, and creativity-oriented writing instruction. The study emphasizes that the success of writing education does not solely depend on teaching strategies but also on teachers’ sensitivity and creativity in facilitating enjoyable and meaningful learning experiences for elementary students.